La implementación de actividades extra-clase basadas en los estilos de aprendizaje individuales para el desarrollo de destrezas lingüísticas del idioma ingles en los estudiantes de primero de bachillerato del colegio “Amelia Gallegos Díaz” de la ciudad de Riobamba, período 2015- 2016 - Guevara Ortiz, Miriam Jimena (2016)
During years the linguistic sills learning have been the principal problem for students learn English due to these skills have treated in isolations, teachers do not work in relation to the students’ learning styles, besides there are not appropriate strategies for helping them to get a good language domain. This fact provides more barriers into the process of the target language. The main goal of the study was to perform an initial evaluation about students’ knowledge scale of linguistic skills in order to determine the necessity for the application of extra – curricular activities based on students’ learning styles. The application of these kinds of activities are applied because of each human being learn in many ways—by seeing and hearing; reflecting and acting; reasoning logically and intuitively; memorizing and visualizing. This fact gives students the opportunity to discover the best strategy to learn and improve the second language acquisition. The Extra-Task activities were applied to the students of First Course of Amelia Gallegos High School of Riobamba City. These were developed according to cycle of four steps which integrated the linguistic skills bearing in mind the most relevant students’ learning styles. These tasks show that matching teaching styles to learning styles can significantly enhance academic achievement, as well as student attitudes and behavior for learning a second language. The time assigned for developing these tasks allowed create a good learning atmosphere where learners were able to remember their prior knowledge and used it in a relaxed environment. They improved their language skills because they recognized their own learning style and enhance others which were not familiarized that is to say, they learned how to learn better. As a final result with the implementation of the extra- curricular activities the students raise the knowledge of their linguistic skills.